THE EFFECT OF EMOTIONAL INTELLIGENCE, INTELLECTUAL INTELLIGENCE AND LEARNING INTEREST ON THE LEVEL OF ACCOUNTING UNDERSTANDING - Nugroho, Paskah Ika; Kiding, Gaby Febyola (Among Makarti, 2023)
ABSTRACTThis study aims to determine the effect of emotional intelligence, intellectual intelligence, and student interest in learning on the level of accounting understanding. This research is a quantitative study with a population of SWCU FEB students from the accounting study program who are still active. Survey method technique is used from 100 students questionnaire data collected and then distributed via email, and other social media using the google form. The analysis technique in this study uses multiple regression techniques. The results of this study indicate that emotional intelligence, intellectual intelligence and interest in learning have a significant positive effect on the level of accounting understanding.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh kecerdasan emosional, kecerdasan intelektual dan minat belajar mahasiswa terhadap tingkat pemahaman akuntansi. Penelitian ini merupakan penelitian kuantitatif dengan populasi mahasiswa FEB UKSW prodi akuntansi yang masih aktif. Teknik pengambilan sampel dalam penelitian ini dilakukan dengan teknik metode survey yang didapatkan dari kuesioner 100 mahasiswa yang dikumpulkan kemudian disebarkan melalui email, dan media sosial lainnya menggunakan google form. Teknik analisis dalam penelitian ini menggunakan teknik regresi berganda. Hasil dari penelitian ini menunjukkan bahwa variabel kecerdasan emosional, kecerdasan intelektual dan minat belajar berpengaruh positif signifikan terhadap tingkat pemahaman akuntansi